Contesting Catholicity : theology for other Baptists - Freeman, Curtis W (Waco, Texas, Baylor University Press, 2014)
In Contesting Catholicity, Curtis W. Freeman offers an alternative Baptist identity, an "Other" kind of Baptist, one that stands between the liberal and fundamentalist options. By discerning an elegant analogy among some late modern Baptist preachers, seventeenth- and eighteenth-century Baptist founders, and early patristic theologians, Freeman narrates the Baptist story as a community that grapples with the convictions of the church catholic.
Includes bibliographical references and index
Keywords: Baptists -- Doctrines; Theology, Doctrinal